KEBIJAKAN DESENTRALISASI PENDIDIKAN DALAM PENINGKATAN MUTU PENDIDIKAN - Fadriati Fadriati; Ritman Hendra (Piwulang: Jurnal Pendidikan Agama Islam, 2023)
This study discusses the decentralization of education, which at first was fully controlled by the central government. With the decentralization of education, local governments have the authority to regulate and control education in their regions in an effort to improve the quality of education. This study uses a qualitative approach with the type of literature study. Data was collected from various journal articles and books that are in accordance with the research topic through content analysis. This type of research is qualitative research. The results of this study show that the decentralization of education is actually fully implemented by the local government so that the impact can be felt by the school community in an effort to improve the quality of education.